PENGARUH PENGETAHUAN PAJAK DAN PERSEPSI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris Pada KPP Pratama Semarang Candisari) (Students' Journal of Accounting and Banking, 2012)
Purpose of this study was to determine the effect of tax knowledge and perceptions of the taxpayer against taxpayer compliance.The population in this study are listed corporate taxpayers in the Tax Office Pratama Candisari Semarang. With a sample of 80 respondents, drawn by using accidental sampling method. The data used are the primary data collected through answers to each question in the questionnaire list. Methods of analysis using multiple linear regression analysis to determine the effect of tax knowledge and perception variables taxpayer against taxpayer compliance.The results of testing showed that, knowledge of tax and the taxpayers perceptions of the council tax affect taxpayer compliance and taxpayer perceptions of criteria of adherence had no effect on taxpayer compliance.Keywords : Tax Knowledge, Perceptions Taxpayer, TaxpayerCompliance